The demographic of urban women's participation in the informal services sector on the subjective economic well -being of households - Othman, Ab Razak; Md. Jusoh, Zuroni; Abd. Rahim@Abdul Wahab, Husniyah; Wan Abdullah, Wan Arnidawati (Human Resource Management Academic Research Society, 2022)
The informal sector is part of economic activities in Malaysia and there is still insufficient information on these economic activities. The informal economy is a label for economic activities that take place outside the framework of public and private institutions. Therefore, this study argues that the level of participation of women working in the informal services sector significantly affects the subjective well -being of household economies in urban areas. Factors of women’s participation in choice and need based on Causal and Utility theory are seen to influence the subjective well -being of the household economy. This study aims to determine the demographic influence of women’s participation in the informal sector, analyzing participation factors by choice and need. This study uses a quantitative approach. A total of 474 respondents representing informal women workers. The field study was conducted between October 2020 to March 2021 at a time when the Covid 19 pandemic was still plaguing Malaysia and the world. This research covers informal women workers in the cities of Selangor, Kuala Lumpur and Putrajaya Malaysia. Urban areas in the state have been selected in this study based on three factors namely major economic factors, geographical factors and strategic location and as a major urban center. One -way ANOVA test were used to look at the relationship and influence between the variables. The results of the study show that there a significant demographic influence of women's participation in the informal sector on the subjective well -being of household economy. The implication of the demographics of women's participation in the informal sector has taken into account by authorities to improve the decent income and providing the good support system for the family members in order to increase the economic wellbeing of the informal sector household in the future.